2022
DOI: 10.4103/ijo.ijo_2838_21
|View full text |Cite
|
Sign up to set email alerts
|

Stromal and endothelial herpes simplex virus keratitis reactivation in the convalescent period of COVID-19 – A case report

Abstract: A 73-year-old lady presented with a white spot and redness in the left eye for 1 month and had been treated elsewhere as a case of fungal keratitis. She had severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral infection 2 months before. Her past ocular history and examination gave a probable diagnosis of herpetic stromal and endothelial keratitis. She responded to oral acyclovir and topical steroid, leading to resolution of stromal edema and inflammation. Anterior chamber fluid polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Undetectable viremia from an initial molecular testing followed by the detection of HHV-1 DNA in a subsequent testing [ 20 , 57 , 71 ], detection of HHV-1 DNA [ 56 , 68 , 74 ] and/or seropositive for HHV-1 IgG [ 60 , 69 , 77 ], history of COVID-19 (recovered) prior to HSV-1 detection, or history of COVID-19 [ 65 ] and corneal ulcer prior to detection of HSV-1 [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undetectable viremia from an initial molecular testing followed by the detection of HHV-1 DNA in a subsequent testing [ 20 , 57 , 71 ], detection of HHV-1 DNA [ 56 , 68 , 74 ] and/or seropositive for HHV-1 IgG [ 60 , 69 , 77 ], history of COVID-19 (recovered) prior to HSV-1 detection, or history of COVID-19 [ 65 ] and corneal ulcer prior to detection of HSV-1 [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Simonnet et al performed systematic testing for EBV, CMV, HHV-6 DNAemia on critically ill COVID-19 patients and observed the virus reactivations in 85% of patients, among which the patients with EBV reactivation required longer hospital length-of-stay [ 17 ]. Skin and ocular manifestations, too, including lesions in multiple regions and herpetic keratitis with risk of blindness, have been observed in patients with Herpesviridae reactivations [ 18 , 19 ]. Liu et al reported HBV reactivation in three COVID-19 patients with a history of chronic HBV infection where an increase in HBV DNA upon admission was noted, with one patient developing cirrhosis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have linked a small number of HSV keratitis cases in patients with COVID-19 since the pandemic outbreak. [29][30][31][32] The immune system characteristics in patients with COVID-19, such as immunosuppression and cytokine storm syndrome, may promote the reactivation of latent viral infections such as HSV. 33,34 The association between HSV and COVID-19 infections suggests that COVID-19 may pose a risk factor for developing or potentially triggering HSV keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2[ 412 ] has been implicated in HSV Keratitis[ 413 , 414 ]. HSK has been reported to relapse post mRNA coronavirus disease 2019 vaccination[ 415 ].…”
Section: Herpes Simplex Keratitis In Immunocompromised Patients: Chal...mentioning
confidence: 99%